Moral issues and Christian responses - Jung, Patricia Beattie (Thomson/Wadsworth, 2003)
The seventh edition of MORAL ISSUES AND CHRISTIAN RESPONSES provides an introduction to contemporary moral issues from decidedly, yet diverse, Christian moral perspectives. This popular anthology explores a variety of pressing topics, including sexuality, prejudice, biomedical ethics, the environment, terrorism, and war.